A Geographic Perspective in the Context of Political Ecology for Understanding Strategic Environmental Assessment in Indonesia - Heinrich Rakuasa; Philia Christi Latue; Yamres Pakniany (Journal of Selvicoltura Asean, 2024)
This research aims to explore the concept of political ecology in the context of the relationship between humans and the environment. Through a qualitative approach, literature analysis, case studies, and interviews were conducted to understand the implementation of the concept of political ecology. The results of the analysis show the complexity of socio-environmental interactions and the scale of political ecology. The findings provide a deeper understanding of the political and cultural dynamics in the representation of "nature". Thus, this research makes an important contribution to understanding political ecology from a geographical perspective. In conclusion, the political ecology approach provides a comprehensive picture and effective solutions in dealing with increasingly complex environmental problems.